THE APPLICATION OF CHARACTER FRIENDLY EDUCATION THROUGH TEACHING HADITH MEMORIZATION AT RAUDHATUL ATHFAL - Harfiani, Rizka (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The objective of this research was to find out the demand for education of friendly character through the teaching of hadit h memorization at Raudhatul Athfal (RA) Ar-Rasyid, Sukamaju Village, Sunggal Sub district, Deli Serdang Regency, North Sumatera. The research used class teaching action with descriptive method. The research subjects were a teacher and 15 students. The data were gathered by conducting observation and data analysis. The formula of the problems as follows: Could teaching hadiths increase friendly character education at Raudhatul Athfal. And the result of the study showed that the teaching planning for application friendly character education through the activity of hadit h memorization was categorized as successful; its implementation was considered successful, and its result was also very good since every aspect of friendly character education highly increased.